Effect of rotary systems and root canal preparation and dentin crack formation - Abulhamayel, Abdulkader Abdulelah; Altukhays, Hamdi Abdullah; Alamri, Hatim Abdullah; Salem, Abdulrahman Ahmad; Farrash, Jummar Ammar; Alshammari, Adulelah Zaid; Alhazmy, Rawan Ibrahim; Alghamdi, Asmaa Ahmed; Alrasheed, Osama Sulaiman; Alanazi, Mona Dabshi; Alotaibi, May Mansour (International Journal Of Community Medicine And Public Health, 2021)
Evidence indicates that root canal preparation is a critical step upon which the prognosis of the endodontic treatment depends. Vertical root fractures can furtherly develop as propagations from the previously formed dentin cracks. Therefore, root canal preparation should be carefully approached with the minimal crack formation and careful dentin removal. Different modalities have been proposed in the literature and rotary systems are most commonly used nowadays. Although the reported efficacy of these modalities is high, evidence shows that they are usually associated with a considerable risk of crack formation. In the present literature review, we have discussed the effects of rotary instrumentation and root canal preparation on dentinal crack formation based on evidence from the different studies in the literature. Our evidence showed that all of the investigated approaches to prepare root canals adequately can result in crack formation. The different rotary instrumentations also showed variable frequencies of developing dentinal cracks, and evidence from some comparative investigations shows that ProTaper modalities are associated with the least frequencies of the events. However, to make a solid conclusion for clinical practice, further research is still needed to validate our current evidence.